Copper diffusion barrier performance of amorphous Ta-Ni thin films - Yan, Hua (2013)
Amorphous Ta–Ni thin films were deposited on Si substrate by magnetron sputtering. The oxygen concentration was adjusted by controlling the substrate bias during the sputtering deposition. Two types of Ta–Ni films, namely Ta67.34Ni27.06O5.60 and Ta73.25Ni26.10O0.65 were employed in the current study. To assess the diffusion barrier performance, Cu/Ta–Ni/Si stacks were fabricated in sequence without breaking the vacuum. The samples were then annealed in vacuum for 30 min at temperatures ranging from 500 °C to 800 °C. SEM, 4-point probe, SIMS and TEM have been used to study the film properties to assess the barrier performance. The films were found to remain stable up to 600 °C without significant Cu diffusion. At 700 °C, Cu diffusion through the barrier film was detected in both types of samples, but with different degree of severity. For the Ta67.34Ni27.06O5.6 barrier film, there was no Cu–Si reaction at 700 °C, while Cu3Si was observed at the Ta73.25Ni26.10O0.65/Si interface. At 800 °C, Cu3Si crystalline phase was found in both samples, and the barrier films have completely lost integrity. This study shows that sputter deposited Ta–Ni amorphous thin films can be used as an effective copper diffusion barrier for microelectronic device fabrication. Incorporation of a few percent of oxygen into the film can retard copper diffusion and interface reaction, which enhances the barrier performance.